Efforts for Rehabilitation and Legal Protection of Underage Narcotics Crime - Parningotan Malau (IHSA Institute, 2022)
Narcotics crime is still a scourge in Indonesia, today the victims are children. Children are assets of survival for humans, the nation, and the state. influence that causes children to become victims of narcotics. Namely depending on external factors or internal factors. To protect children's rights to ensure a decent life, there is a need for legal protection. Violations of specific criminal offenses for Narcotics which regulate in general are regulated in the provisions of Law no. 35 of 2009 concerning Narcotics. In addition to the provisions on Rehabilitation Efforts, and special rules governing juvenile justice are contained in Law no. 11 Year 2012.